COMPARISON OF FEMUR LENGTH WITH GESTATIONAL AGE INCLUDING OR EXCLUDING THE SPUR OF FEMUR: comparison of FL and GA - Irram, Saadia; Ali, Abid; Naeem, Muhammad Ahmad; Maqsood, Mahnoor; Ashraf, Nadia; Muzafar, Saba; Mazhar, Mehlab; Kalsoom, Ume (Medical Science Journal for Advance Research, 2023)
Background: Femur is a long bone that measures gestational age and contributes to human height and weight, but can also be affected by growth retardation or skeletal growth abnormalities. Objective: To compare the effect of femur length on gestational age of fetus using ultrasonography. Methods: The research was a four-month crossectional study carried out in a private hospital in Tehsil Kharian, District Gujrat, Pakistan. Data was obtained using a simple sampling strategy from December 2022 to March 2023. As a matter of convenience, a sample size of 100 patients was chosen. In compliance with ethical norms described by the research committee, the data was obtained after the patient granted informed consent. Data was entered and analyzed using SPSS version 20.0. Results: This study revealed that 42% females were in early 2nd trimester of gestation, 31% females were in late 2nd trimester of gestation, 21% females were in early 3rd trimester of gestation and only 6% females were at term. Conclusion: In conclusion, based on femur length, ultrasonography is sensitive and accurate in predicting fetal gestational age.